The Early Environment and Schooling Experiences of High-Technology Entrepreneurs: Insights for Entrepreneurship Education - Kourilsky, Marilyn L.; Walstad, William B. (Senate Hall, 2003)
How do we prepare current and future generations of learners to anticipate, recognize, and act on high-technology opportunities so that they can join the ranks of future entrepreneurial leaders in our nation's emerging knowledge-based and technology-oriented economy? As one of the natural first steps in addressing the above questions, this study investigates for existing high-technology entrepreneurs the motivations, influencing factors, and obstacles encountered during their youth and early adult years. The authors developed an extensive survey instrument to probe the desired information, and the study's data was collected from a random national sample of 1,001 owners/founders of high-technology businesses with under 200 employees. Major findings are reported with respect to age of initiation; time from idea to action; key trigger events, reasons, and other factors influencing the high-technology venture initiation decision; best sources of preparation; and insufficient education as a major obstacle theme. The findings suggest an important potential role for education in general and entrepreneurship education in particular. One potential strategy recommended is to craft cross-cutting educational partnerships that carefully blend entrepreneurship education, technology content-specific education, and high-technology venture experience at both the high school and college levels.
Keywords: high-technology|entrepreneurship|entrepreneurship education|early influences|national survey